(3GdMLI aj TQM (B" (3GdbQGAGJ GdSHY (B"s - (3CMeO Hf ehSi Hf GdYHGS GdJejej, CHh HcQ Hf eLGgO , (B324 (3g` s; (3GdMSf Hf CMeO Hf YHO GdZaGQ GdaGQSqj GdCUd, CHh Ydj, (B377 (3g`s
(3ChdgG (B:s
(3jHJOF HHbjI ShQI GdHbQI s
(3BNQgG (B:s
(3hjfJgi HBNQ ShQI GdCfYGe s
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B8 s
(3eUOQ GbJfGA GdCUd (B:s
(3eQGO edd (B(7) s
Keywords: (3GdbQGAGJ hGdJLhjOs